Principles of Cord Activation During Spinal Cord Stimulation. (June 2014) - Molnar, Gabriela; Barolat, Giancarlo
Abstract : Objectives: This study aims to review some of the basic principles of extracellular electrical stimulation used in spinal cord stimulation therapy for intractable pain. Materials and Methods: Spinal cord stimulation has been used therapeutically for more than 40 years. We present the basic principles of extracellular stimulation on which the therapy is based, describe electrode operation and current configurations, and explain the implications of these technological advances for the clinical application of spinal cord stimulation. Results: Computational studies of coupled electric field and neuron models have significantly advanced our understanding of the therapeutic effects of neurostimulation. Neurostimulation is intended to obtain maximal selectivity of desired neural elements while avoiding those resulting in side‐effects. Preferential stimulation of the dorsal columns is achieved with a narrow spacing between electrodes using bipolar or tripolar electrode configurations. Stimulus parameters such as amplitude and pulse width may be used to selectively control which neuronal elements are excited during stimulation. Conclusions: A better understanding of the interaction between electric fields and the targeted neural elements may guide the selection of stimulation parameters in contemporary neurostimulators and lead to continuing advances in engineering solutions for therapeutic spinal cord stimulation.